2015
DOI: 10.1682/jrrd.2014.12.0300
|View full text |Cite
|
Sign up to set email alerts
|

Interrater reliability of mechanical tests for functional classification of transtibial prosthesis components distal to the socket

Abstract: Abstract-Substantial evidence suggests that the design and associated mechanical function of lower-limb prostheses affects user health and mobility, supporting common standards of clinical practice for appropriate matching of prosthesis design and user needs. This matching process is dependent on accurate and reliable methods for the functional classification of prosthetic components. The American Orthotic & Prosthetic Association developed a set of tests for L-code characterization of prosthesis mechanical pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…Although there are notable exceptions when commercial prostheses characterization is included to correlate mechanical function with user outcomes 4244 , these studies are constrained within the range of prosthesis properties available through commercial devices. Recently, standardized bench tests were proposed to classify prosthetic feet based on mechanical properties such as stiffness and energy loss 38, 45 , which could enhance objectivity of device classification.…”
Section: Optimizing Passive Prosthesis Design Through Parametric Smentioning
confidence: 99%
“…Although there are notable exceptions when commercial prostheses characterization is included to correlate mechanical function with user outcomes 4244 , these studies are constrained within the range of prosthesis properties available through commercial devices. Recently, standardized bench tests were proposed to classify prosthetic feet based on mechanical properties such as stiffness and energy loss 38, 45 , which could enhance objectivity of device classification.…”
Section: Optimizing Passive Prosthesis Design Through Parametric Smentioning
confidence: 99%
“…dynamic keel, cushioned heel). 18,24 However, these classifications are based on displacement and energy return that may be problematic if footwear is not considered. For example, all three low mobility prostheses designs (Multiaxial, Single-axis, and SACH) displayed stiffness that allowed for keel displacement at 1230 N to qualify them as rigid per suggestions of the AOPA classification guidelines (<25 mm), but exceeded this threshold when combined with the trainer and hiking boot to be considered flexible (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…The setup and mechanical tests used in this study were adapted from those described in the American Orthotic & Prosthetic Association (AOPA) Foot Project Report 18 to characterize prosthesis mechanical behavior, which have been demonstrated to have excellent repeatability, 24 and are modeled after standardized methods for characterizing prosthesis mechanical properties independent of the user. 11,12…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, although many studies have compared suspension systems in prostheses, types of joints, and different types of sockets [ 10 , 22 , 23 ], there is no any study investigating the effectiveness of socket types. However, most of these studies reported that a test socket was used before the placement of a permanent socket [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%